2014
DOI: 10.1016/j.diagmicrobio.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbapenem-resistant Acinetobacter baumannii in Brazil (2008–2011): countrywide spread of OXA-23–producing clones (CC15 and CC79)

Abstract: The study investigated the genetic relationship of carbapenem-resistant Acinetobacter baumannii clinical isolated from inpatients during 2008-2011 from 11 Brazilian states. Antimicrobial susceptibility profile was determined by disc diffusion method and Etest. Polymerase chain reaction was applied for carbapenemase genes, and ISAba1. Isolates were subjected to pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) for molecular typing. Most of the isolates showed high resistance rates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 26 publications
4
38
0
4
Order By: Relevance
“…We found that bla NDM-1 , bla , and armA were collocated on plasmids in 8/25 (32%) extracted isolates. This is in accordance with previous reports showing that bla , bla NDM-1 , and armA genes in A. baumannii are mostly located on plasmids (16,19,20). Similarly, AMEencoding genes [ant (2), aad, aac (6), aph, and aac(3)] were found to be plasmidic.…”
Section: Aac(6)-a4supporting
confidence: 81%
See 1 more Smart Citation
“…We found that bla NDM-1 , bla , and armA were collocated on plasmids in 8/25 (32%) extracted isolates. This is in accordance with previous reports showing that bla , bla NDM-1 , and armA genes in A. baumannii are mostly located on plasmids (16,19,20). Similarly, AMEencoding genes [ant (2), aad, aac (6), aph, and aac(3)] were found to be plasmidic.…”
Section: Aac(6)-a4supporting
confidence: 81%
“…All the MHT-negative isolates (25/150) were found to be negative for the tested carbapenemase-encoding genes. It is well known that bla and bla OXA-51 are regulated in part by ISAba1, which may be located upstream of these genes acting as a promoter and resulting in the overexpression of these genes and in a high level of carbapenem resistance (16,17). In our study ISAba1 was found upstream of the bla OXA-23 -like and bla OXA-51 -like genes in 91.3% (137/150) and 4.7% (7/150) of our isolates, respectively.…”
mentioning
confidence: 99%
“…It is remarkable that we detected the occurrence of strains belonging to CC25 (ST25, three strains). CC25 had already been detected in Brazil at low frequencies, and those strains were associated with the bla OXA-23 (16) and bla NDM-1 (21) genes. Although we did not detect the bla NDM gene in our strains, NDM enzymes are emerging in the Brazilian territory (21), including in different Acinetobacter species (22), which is an alert for the need for surveillance of this threatening combination.…”
mentioning
confidence: 99%
“…The studied strains were detected 4 years apart and belonged to the same PFGE clone; however, the clone source and reservoir remained undetermined. In fact, bla OXA-58 is rarely reported in Brazil (23), where bla OXA-23 and bla have been the most predominant CHDL genes (23,24). The presence of carbapenemase-encoding genes in non-baumannii species exhibiting decreased susceptibility to polymyxins is a cause of great concern, because it drastically limits the available therapeutic options for treatment of such infections.…”
mentioning
confidence: 99%